Design, Synthesis, and In Vitro Kinetics Study of Atenolol Prodrugs for the Use in Aqueous Formulations - Rafik Karaman; Alaa Qtait; Khulod Khayyat Dajani; Saleh Abu Lafi (The Scientific World Journal)
Based on DFT, MP2, and the density functional from Truhlar group (hybrid GGA: MPW1k) calculations for an acid-catalyzed hydrolysis of nine Kirby’s N-alkylmaleamic acids and two atenolol prodrugs were designed. The calculations demonstrated that the amide bond cleavage is due to intramolecular nucleophilic catalysis by the adjacent carboxylic acid group and the rate-limiting step is determined based on the nature of the amine leaving group. In addition, a linear correlation of the calculated and experimental rate values has drawn credible basis for designing atenolol prodrugs that are bitterless, are stable in neutral aqueous solutions, and have the potential to release the parent drug in a sustained release manner. For example, based on the calculated B3LYP/6-31 G (d,p) rates, the predicted t1/2 (a time needed for 50% of the prodrug to be converted into drug) values for atenolol prodrugs ProD 1-ProD 2 at pH 2 were 65.3 hours (6.3 hours as calculated by GGA: MPW1K) and 11.8 minutes, respectively. In vitro kinetic study of atenolol prodrug ProD 1 demonstrated that the t1/2 was largely affected by the pH of the medium. The determined t1/2 values in 1N HCl, buffer pH 2, and buffer pH 5 were 2.53, 3.82, and 133 hours, respectively.